Pengaruh Motivasi Dan Kepemimpinan Terhadap Kinerja Pegawai Di Kantor Kecamatan Anggeraja Kabupaten Enrekang - Muh. Ashari Baharuddin; Zainal Ruma; Uhud Darmawan Natsir; Agung Widhi Kurniawan; Burhanuddin Burhanuddin (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This research aims to determine the influence of motivation and leadership on employee performance at the Anggeraja District Office, Enrekang Regency. The variables of this research are Motivation (X1), Leadership (X2) as the independent variable and Performance Volume (Y) as the dependent variable. The population in this study were 25 employees at the home office of the sub-district head of Anggeraja sub-district, Enrekang Regency who were also the samples. The sampling technique in this research was carried out using a simple random sampling method (Simple Random Sampling method). Data collection was carried out using a questionnaire. The data analysis technique used is simple linear regression analysis using SPSS 25.00 for Windows Based on the research results and discussion, the conclusion in the research is that Motivation (X1) has t count 6.429 ≥ t table 2.069 and a significant value of 0.000 < 0.05. This can be interpreted as meaning that motivation has a positive and significant effect on employee performance at the Anggeraja District Office, Enrekang Regency. The higher the employee's motivation at work, the better the employee's performance in carrying out their duties. Leadership (X2) is 2.699 ≥ t table 2.069 and a significant value of 0.013 < 0.05 can be concluded that leadership has a positive and significant effect on performance. Employees who have a leadership attitude both in leading themselves and their subordinates and co-workers can have good performance at work.